1979
DOI: 10.1148/131.2.371
|View full text |Cite
|
Sign up to set email alerts
|

Pseudohyperphalangism in Fetal Dilantin Syndrome

Abstract: Apparent distal hyperphalangism was observed in three siblings with fetal Dilantin syndrome. Other stigmata of this syndrome were also present. The anomaly in these patients was cuased by division of an otherwise normal phalanx, as opposed to the case in true hyperphalangism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1981
1981
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…These findings resemble those seen with fetal hydantoin exposure ( Jones, 2006 ), and indeed patient 2 was given this diagnosis initially. Other evidence that could support this diagnosis is her mild growth deficiency and, although the absence of the proximal epiphyseal center of the pollex may be a more distinctive feature of TBS, this finding has also been observed rarely in presumed fetal hydantoin embryopathy ( Wood and Young, 1979 ; Johnson and Goldsmith, 1981 ). However, the clinical diagnosis of TBS was made because her craniofacial features and hallux appearance more closely matched the observations made previously in other affected individuals with TBS, with this diagnosis validated molecularly upon the recent identification of the causative gene; both patients characterized in this report harbor pathogenic mutations ( Simons et al , 2014 ).…”
Section: Discussionmentioning
confidence: 85%
“…These findings resemble those seen with fetal hydantoin exposure ( Jones, 2006 ), and indeed patient 2 was given this diagnosis initially. Other evidence that could support this diagnosis is her mild growth deficiency and, although the absence of the proximal epiphyseal center of the pollex may be a more distinctive feature of TBS, this finding has also been observed rarely in presumed fetal hydantoin embryopathy ( Wood and Young, 1979 ; Johnson and Goldsmith, 1981 ). However, the clinical diagnosis of TBS was made because her craniofacial features and hallux appearance more closely matched the observations made previously in other affected individuals with TBS, with this diagnosis validated molecularly upon the recent identification of the causative gene; both patients characterized in this report harbor pathogenic mutations ( Simons et al , 2014 ).…”
Section: Discussionmentioning
confidence: 85%
“…Distal hyperphalangism has been observed in siblings with fetal dilantin syndrome. 16 We have observed personally 16 cases of hyperphalangism in the past 25 years. 18 We consider this an uncommon congenital anomaly.…”
Section: Discussionmentioning
confidence: 98%
“…The involved digits were tapered and the nails were dyplastic. 10 The phalangeal anomalies were demonstrated to be present at birth, and the phalanges never developed epiphyses, suggesting that the abnormality is caused by the division of an otherwise normal phalanx and not a true hyperphalangism, that is, a pseudohyperphalangism. Experimental studies on rats have demonstrated that anticonvulsant drugs may interfere with the regulation of chondrocyte activity and matrix synthesis.…”
Section: Thalidomidementioning
confidence: 99%